Penerapan Strategi Pembelajaran Peningkatan Kemampuan Berpikir (SPPKB) Terhadap Hasil Belajar Siswa Pada Tema 7 Indahnya Keragaman Di Negeriku - Kristina Sopia Ambarita; Dewi Anzelina; Novalina Sembiring; Reflina Sinaga; Ester Julinda Simarmata (Journal on Education, 2023)
This study aims to improve student learning outcomes after the application of the thinking skills improvement learning strategy (SPPKB) Theme 7 Beautiful Diversity in My Country in Class IV SD Negeri 067244 Medan Selayang in Class IV SD Negeri 067244 Medan Selayang. The results of this study can be seen from students who completed their learning outcomes in post test 1 there were 11 students who were complete, who were complete (39%) and students who did not complete their learning outcomes were 17 students (61%). In the second cycle post test, obtained student learning outcomes from 28 students there were 25 students who completed their learning outcomes (89%), while as many as 3 students who did not complete their learning outcomes were (11%). The results of the data above show that student scores have increased from the implementation of the post test of each cycle. Based on the data obtained from the average learning outcomes in the first cycle post test and the second cycle post test, it can be seen that there is an increase. In the first cycle post test, the average learning outcome was 66.68 while the second cycle post test average learning outcome increased to 88.75. Based on the increase obtained from the data on student learning outcomes, it can be seen that from the first cycle post test to the second cycle post test experienced an increase of 22.07. It can be concluded that student learning outcomes increased after the implementation of the learning strategy for improving thinking skills (SPPKB) Theme 7 Beautiful Diversity in My Country in Class IV of SD Negeri 067244 Medan Selayang in Class IV of SD Negeri 067244 Medan Selayang.